2017
DOI: 10.1186/s13063-017-1934-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative costs and activity from a sample of UK clinical trials units

Abstract: BackgroundThe costs of medical research are a concern. Clinical Trials Units (CTUs) need to better understand variations in the costs of their activities.MethodsRepresentatives of ten CTUs and two grant-awarding bodies pooled their experiences in discussions over 1.5 years. Five of the CTUs provided estimates of, and written justification for, costs associated with CTU activities required to implement an identical protocol. The protocol described a 5.5-year, nonpharmacological randomized controlled trial (RCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Our experience on more recent trials is that these two tools may considerably underestimate the research nurse time necessary to undertake essential research procedures, threatening the success of the recruitment effort and the integrity of research data. Published workload models estimating staff resource for RCTs [74–79] are often criticised for over-simplicity, and their use can lead to staff burnout and poor implementation [8082]. The rise of surgical trainee networks in the UK as a force in recruitment may go some way to compensating for the pressures on costs in public sector research, where trainees can be incentivised and co-ordinated to recruit and follow up study participants [83].…”
Section: Discussionmentioning
confidence: 99%
“…Our experience on more recent trials is that these two tools may considerably underestimate the research nurse time necessary to undertake essential research procedures, threatening the success of the recruitment effort and the integrity of research data. Published workload models estimating staff resource for RCTs [74–79] are often criticised for over-simplicity, and their use can lead to staff burnout and poor implementation [8082]. The rise of surgical trainee networks in the UK as a force in recruitment may go some way to compensating for the pressures on costs in public sector research, where trainees can be incentivised and co-ordinated to recruit and follow up study participants [83].…”
Section: Discussionmentioning
confidence: 99%
“…As the information available in the public domain on the sponsor cost of a trial is limited to clinical trial units in the UK [32], we based our sponsor costs on the past real-life experience of the authors: together we have about 100 years of experience in managing clinical trials in the biopharmaceutical industry, a contract research organisation (CRO), hospitals and an academic sponsor organisation. In addition, the initial tool was fine-tuned based on consultancy provided by an experienced former director of a CRO (BV, see Acknowledgements).…”
Section: Methodsmentioning
confidence: 99%
“…the practical management of clinical trials research [15]. However, research in both the USA and UK has demonstrated that CTUs have markedly different histories and infrastructure, which impact on the ways that they manage clinical trials [16,17].…”
Section: Introductionmentioning
confidence: 99%